2006
DOI: 10.1177/014860710603000140
|View full text |Cite
|
Sign up to set email alerts
|

IV Hypertonic Glucose Stimulates the Exocrine Pancreas in Rat

Abstract: I.v. glucose results in atrophy of the exocrine pancreas, elevates the amylase in pancreas, but suppresses the stimulatory effect of cholecystokinin on the exocrine pancreas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…19,36 Intraduodenal glucose does not stimulate the pancreas, and exclusive IV glucose feeding results in marked pancreatic atrophy. 36 However, data on the effect that IV glucose has on exocrine pancreatic function is conflicting, with evidence pointing to both decreases 37 and increases 38 in secretory and synthetic function. What is apparent is that luminal fats and proteins stimulate pancreatic exocrine function, IV amino acids mitigate pancreatic hypotrophy, and IV glucose may stimulate synthesis of pancreatic enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…19,36 Intraduodenal glucose does not stimulate the pancreas, and exclusive IV glucose feeding results in marked pancreatic atrophy. 36 However, data on the effect that IV glucose has on exocrine pancreatic function is conflicting, with evidence pointing to both decreases 37 and increases 38 in secretory and synthetic function. What is apparent is that luminal fats and proteins stimulate pancreatic exocrine function, IV amino acids mitigate pancreatic hypotrophy, and IV glucose may stimulate synthesis of pancreatic enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…A series of studies suggested PN treatment could lead to dysfunction and atrophy of the pancreas. Fan et al reported that pancreas weight and the concentration of pancreatic amylase were lower in the PN group compared with control group [14] and found that pancreatic atrophy and dysfunction might be the possible mechanism [25]. They concluded that intravenous hypertonic glucose resulted in atrophy of the pancreas by the suppression of the stimulatory effect of cholecystokinin on pancreas [26].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that TPN or the absence of food in the GI tract can result in an atrophy of the pancreas, including histological damage and dysfunction of the pancreas (O’ Keefe et al., 2003; Fan and Andren‐Sandberg, 2006). These findings have suggested that enteral factors are important for maintaining normal morphology and physiology of the pancreas.…”
Section: Discussionmentioning
confidence: 99%
“…These findings have suggested that enteral factors are important for maintaining normal morphology and physiology of the pancreas. The atrophy and functional changes resulting from TPN involve multiple factors; the absence of hormonal stimuli seems to be one of the reasons (Fan and Andren‐Sandberg, 2006).…”
Section: Discussionmentioning
confidence: 99%